Neutrophil to lymphocyte ratio and correlation with hepatic fibrosis in patients with chronic hepatitis B - Shivalingappa, Umashankar Uyigowdanahally; Ramasamy, Akilandeshwari Alagan; Muhammed, Kani Shaikh; A., Anand; N., Arun (International Journal of Research in Medical Sciences, 2022)
Background: Chronic hepatitis B (CHB) is a dynamic condition involving interaction between the hepatitis B virus, hepatocyte and host immune system. Neutrophil-lymphocyte ratio (NLR) is a cheap, easily available bedside inflammatory marker. The aim of the study was to assess the role of NLR to assess the fibrosis in CHB patients Methods: It was a prospective cross-sectional study done between January 2021-December 2021, 61 patients with CHB of age 16-50 years were included. Basic demographic and laboratory parameter were assessed. Fibrosis was assessed using fibroscan (ECHOSENS) 502 model. Using NLR cut-off of 1.9 fibrosis was assessed in different groups. Results: The mean age was 34±13.1 years, 66% were male patients. The mean haemoglobin, total count, platelet counts were 11.3±2.1 g/dl, 7250±2100 cells/ml, 146000±26000/ml respectively. The 38 (62.3%) patients were HBeAg positive and 23 (37.7%) patients HBeAg negative. The 28 (45.1%) patients had no significant fibrosis (<8 kpa) and 33 (54.09%) patients had significant fibrosis (>8 kpa). The 33 patients with significant fibrosis 30 patients had NLR of less than 1.9 and 3 had NLR>1.9. The 28 patients who had fibrosis of less than 6.5 kpa, 26 had NLR more than 1.9 and 2 patients with less than 1.9. Mean N/L ratio values were notably lower in cases with advanced fibrosis when compared to individuals with no/minimal fibrosis (p<0.0001). APRI was among 0.32±0.18 and 0.86±0.21 among patients with NLR<1.9 and >1.9 respectively (p=0.0001) Conclusions: Decreased N/L ratio is significantly associated with fibrosis severity and can be utilised to identify patients with advanced disease.